Zero-sum beliefs across age and generations - Vazquez-Olivieri, Veronica; Kricheli-Katz, Tamar; Keysar, Boaz (Journal of experimental psychology. General, 2025)
Zero-sum beliefs, the idea that for one person to gain another must lose, are pervasive even in situations that are not zero-sum. This undermines judgment across contexts such as interpersonal relations, labor relations, public policies, international relations, and economic transactions. Here, we investigate how zero-sum beliefs differ as people age and why it happens. Across four experimental studies ( = 2,473), we discovered that older people hold fewer zero-sum beliefs than younger individuals. We show that this is partly a result of adopting more positive thinking than younger people and perceiving resources as less scarce. Using World Values Survey data ( = 207,171), we then find that this reduction in zero-sum beliefs is a function of both age and generation: The older people get, the less they hold zero-sum beliefs, the generation who is older today is less zero-sum than today's young generation. When people perceive situations that are not zero-sum as if they were zero-sum, it undermines the potential to increase mutual gains. The reduction of this bias with age could provide older people with opportunities they missed out on when they were younger. These findings are important in understanding the process of aging, and they have implications for negotiations and policy. (PsycInfo Database Record (c) 2025 APA, all rights reserved).